EDUKASI MASYARAKAT TENTANG ATURAN DAN SIKAP SAAT MEMBELI MAKANAN KADALUARSA - Marwati Santoso Putri, Filu (ABDIMAS Madani, 2022)
Economic activity is felt alive if it creates an atmosphere that supports the smooth production of goods and services from producers to consumers. Globalization is characterized by free trade, but has not provided much improvement to the economy in Indonesia. There is fraud in almost every line of life, especially in the economic field. What's more, fraud is spreading from traditional markets to supermarkets. As victims of this condition, the people of Nyamplung, Kradenan, Srimulyo, Piyungan, Bantul hamlets have not yet understood the anticipatory steps and the laws they must take in this condition. The community service program has been carried out in accordance with the plan and has been well completed. The activity is only carried out for one day with a face-to-face education model. The people involved are residents of the hamlets of Nyamplung, Kradenan, Srimulyo, Piyungan, Bantul. The educational method used is lectures with printed media and power points followed by focus group discussions and evaluations. During the activity process from beginning to end, the community seemed interested and focused on the material provided by the service. The results of the evaluation of the activities also stated that all of the community understood the educational materials provided by the service.